Decision Tree Implementation in IT Job Recommendation System - Widayati, Yohana Tri; Widjaja, Stephanus; Wicaksono, Adityo Putro; Gondohanindijo, Jutono; Putri, Christine Cecillia (Jurnal Transformatika, 2024)
Employment is the primary activity that humans engage in to generate income. With the advancement of technology and research, there are many new job opportunities leading to confusion in choosing a job path. This leads to individual confusion in making job choices. Ignorance of one’s own talents and personality, as well as ignorance of the various options available, can be the source of this ignorance. This research aims to develop a Decision Tree model to assist users in determining the appropriate IT field. The system uses AI Project Cycle and data processing tools such as Google Collaboratory, which is based on Python programming language. The results show that the Decision Tree algorithm can be applied to recommend jobs in the IT field to help users find suitable fields in the IT field.